2019
DOI: 10.1016/j.celrep.2019.05.088
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Glial Differentiation in Schizophrenia May Be Relieved by Suppression of SMAD4- and REST-Dependent Signaling

Abstract: Astrocytic differentiation is developmentally impaired in patients with childhood-onset schizophrenia (SCZ). To determine why, we used genetic gain- and loss-of-function studies to establish the contributions of differentially-expressed transcriptional regulators to the defective differentiation of glial progenitor cells (GPCs) produced from SCZ patient-derived iPSCs. Negative regulators of the BMP pathway were upregulated in SCZ GPCs, including BAMBI, FST and GREM1, whose over-expression retained SCZ GPCs at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 79 publications
4
25
1
Order By: Relevance
“…Very recent evidence links a range of disorders spanning from Huntington’s disease to schizophrenia to a general decline in K + channel expression and a resultant increase in interstitial [K + ] o . Restoration of Kir4.1 channel expression or replacement of defective astrocytes were both sufficient to restore [K + ] o and neural function in animal models ( Benraiss et al, 2016 ; Liu et al, 2019 ; Tong et al, 2014 ; Windrem et al, 2017 ). Such findings may have considerable importance for the understanding of cognitive disturbances in neurodegenerative diseases and psychiatric disorders.…”
Section: Past and Future Perspectivesmentioning
confidence: 98%
“…Very recent evidence links a range of disorders spanning from Huntington’s disease to schizophrenia to a general decline in K + channel expression and a resultant increase in interstitial [K + ] o . Restoration of Kir4.1 channel expression or replacement of defective astrocytes were both sufficient to restore [K + ] o and neural function in animal models ( Benraiss et al, 2016 ; Liu et al, 2019 ; Tong et al, 2014 ; Windrem et al, 2017 ). Such findings may have considerable importance for the understanding of cognitive disturbances in neurodegenerative diseases and psychiatric disorders.…”
Section: Past and Future Perspectivesmentioning
confidence: 98%
“…The only predicted activated state was identified in S1.3 (activation z-scores of 2.000; 5.280 and P value of overlap 1.68E-05; 7.28E-05). In our S2.3 findings, miR-137-3p was an upstream regulator of ADRB1, ASPH, CACNB2 [36], CTNA3 [37], GREM1 [38], and ZEB2 (an ELAVL1 [41]. In the schizophrenia upstream regulator comparisons, all miRNAs were activated (S1.3, S3.3), while in S2.3, of 2 miRNAs represented, neither was activated.…”
mentioning
confidence: 59%
“…responded differentially to IL1β-induced inflammation. Liu, et al 7 reported that astrocyte differentiation and maturation are impaired in glial progenitor cells derived from childhood-onset SCZ. Similar to our study, they found a number of potassium-related genes to be differentially expressed in SCZ glial cells, and further detected reduced uptake of potassium in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Human induced pluripotent stem cell (hiPSC) models have been used to explore neuropathological abnormalities in patients with SCZ, but so far, the main focus has been on neuronal pathophysiology, while the contribution of astrocytes has received much less attention. One study using hiPSC-derived astrocytes obtained from patients with SCZ showed impaired astrocyte maturation related to enhanced BMP signaling pathway in childhood-onset patients with SCZ 7 , and another study found attenuated CCL20 response and T cell recruitment in patients with SCZ after IL-1 exposure 8 . Moreover, transplanted human iPSC-derived glial progenitors obtained from childhood-onset SCZ patients have shown delayed astrocytic differentiation and abnormal astrocyte morphologies as well as behavioral abnormalities in mouse brains 9 .…”
Section: Neuropharmacological Studies Have Implicated Abnormal Dopamimentioning
confidence: 99%